OP0270 Long-term prognosis in chronic plantar fasciitis based on disease duration and ultrasonic changes. (15th June 2017) - Hansen, L; Fredberg, U; Krogh, TP; Ellingsen, T; Hansen, LB
Abstract : Background: Plantar fasciitis (PF) affects 7–10% of the population over a lifetime but the long-term prognosis is unknown. This study is the greatest within the long-term prognosis of PF and have the longest follow-up time. Objectives: The aim was to assess the long-term prognosis of chronic PF based on duration of symptoms and ultrasonic changes (tendon thickness, heel spur, echogenecity and heel fat pad) and assess if any baseline cohort characteristics had an impact on the prognosis (sex, BMI, age, smoker status, physical work/sport and bilateral pain). Methods: At baseline (2001–11) 269 patients were diagnosed with PF based on symptoms and ultrasound findings. At follow-up (2016) all the participants were invited to participate in the project. Everyone was interviewed and offered a new ultrasound examination of their plantar fascia at both feet. Results: 174 (65%) participated in the study, 52% women and 48% men and 137 had an additional US examination. 54% of the participants were asymptomatic at follow-up (asymptomatic group) and the mean duration of symptoms were 725 days (range 41–4018). 46% still had symptoms (symptomatic group). The follow-up period was 9.7 years (range 4.7–27.3). The risk of having chronic PF were 45.6% (95% CI 37.9–53.0) 10 years after debut of symptoms (figure 1 ). A multiple cox regression analysis found that women (p<0.01) and participants with bilateral heel pain (p<0.01) had a worse prognosis. The hazard rate ratio was 0.49 (95% CI 0.30–0.80) for women (every time 100 men were getting cured pr. year only 49 women were cured pr. year) and 0.33 (95% CI 0.15–0.72) for participants with bilateral heel pain (every time 100 with unilateral pain were cured pr. year only 33 with bilateral pain were cured pr. year). The remaining baseline cohort characteristics (all p's>0.05), tendon thickness (p=0.49) and heel spur (p=0.88) did not have an impact on the prognosis (table 2). The mean tendon thickness was at baseline 6.9 mm in the asymptomatic group and 6.7 mm in the symptomatic group. The tendon thickness was reduced significantly to 4.3 mm at follow-up in both groups (both p's<0.01). Only 24% in the asymptomatic group had a normal tendon thickness and echogenicity at follow-up (6% in the symptomatic group). The participants had in average tried 3.8 (range 1–9) different treatment modalities and 93% received an ultrasound guided steroid injection at baseline. 11% of them were permanently cured 1 month after the injection despite symptoms for an average of 334 days' prior the injection. No atrophy of the heel fat pad was found in the sick foot who got the steroid injections compared to the contralateral foot that did not get the injection (p=0.66). Conclusions: 45.6% had PF 10 years after debut of symptoms. The asymptomatic participants had in average plantar fasciitis for 725 days. The prognosis was significantly worse for women and participants with bilateral pain. The tendon thickness decreased over time no matter of symptoms and had no impact on the prognosis, neither did heel spur. Only 24% of the asymptomatic participants had a normal tendon on ultrasound at long-term follow-up. Ultrasound guided steroid injection did not give atrophy of the heel fat pad in long-term follow-up. Acknowledgements: The project was financed by The Danish Rheumatism Association and The Research Funds of Hospital Unit Central Jutland Disclosure of Interest: None declared